2019
DOI: 10.7554/elife.49314
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of cytokine receptor trafficking determine signaling and functional selectivity

Abstract: Cytokines activate signaling via assembly of cell surface receptors, but it is unclear whether modulation of cytokine-receptor binding parameters can modify biological outcomes. We have engineered IL-6 variants with different affinities to gp130 to investigate how cytokine receptor binding dwell-times influence functional selectivity. Engineered IL-6 variants showed a range of signaling amplitudes and induced biased signaling, with changes in receptor binding dwell-times affecting more profoundly STAT1 than ST… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 86 publications
(128 reference statements)
8
53
0
Order By: Relevance
“…Indeed, several studies have reported the ability of STAT3 to inhibit transcription induced by other STATs (Costa-Pereira et al, 2002;Ray et al, 2014;Yang et al, 2011), suggesting that STAT3 activating cytokines may elicit their functions by disrupting transcriptional programs induced by other cytokines. In agreement with this model, we recently reported that IL-6, another STAT3 activating cytokine, promoted strong STAT3 binding to chromatin, but poor gene expression (Martinez-Fabregas et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Indeed, several studies have reported the ability of STAT3 to inhibit transcription induced by other STATs (Costa-Pereira et al, 2002;Ray et al, 2014;Yang et al, 2011), suggesting that STAT3 activating cytokines may elicit their functions by disrupting transcriptional programs induced by other cytokines. In agreement with this model, we recently reported that IL-6, another STAT3 activating cytokine, promoted strong STAT3 binding to chromatin, but poor gene expression (Martinez-Fabregas et al, 2019).…”
Section: Discussionsupporting
confidence: 81%
“…WTM showed a poor activation of STAT1 and STAT3 with amplitudes of activation reaching less than fifty percent of those elicited by WTD ( Figure 3b). While WTD, R5A11D and R5A11M showed a similar pSTAT1 to pSTAT3 ratio, WTM's clear bias towards pSTAT3 (Figure 3d), agrees with previous observations from our laboratory describing biased signaling by short-lived cytokine-receptor complexes (Martinez-Fabregas et al, 2019). R5A11M induced activation of both STAT1 and STAT3 to levels comparable to those induced by the dimeric cytokines at saturating doses, suggesting that the defective signaling elicited by WTM results from its weak IL-10Rβ binding affinity (Figure 3b and 3c).…”
Section: Il-10 Variants Exhibit Enhanced Signaling Activities In Humasupporting
confidence: 91%
See 3 more Smart Citations